2006
DOI: 10.1163/156854106778614074
|View full text |Cite
|
Sign up to set email alerts
|

Ergot alkaloids are not essential for endophytic fungus-associated population suppression of the lesion nematode, Pratylenchus scribneri, on perennial ryegrass

Abstract: Several endophytic fungi of the genus Neotyphodium form symbiotic associations with Lolium spp. grasses and are renowned for production of bioactive alkaloids such as ergot alkaloids. Some of these endophytes make their grass partners less suitable as hosts for endoparasitic nematodes, including Pratylenchus spp. The potential for ergot alkaloids to affect nematode motility was investigated in vitro. Ergovaline, the ergot alkaloid pathway end product of several Neotyphodium spp., was the only ergot alkaloid te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…Ky312 is a poor host for stunt and ring nematodes, but a good host for spiral nematode. In previous work, the wild type endophyte has been shown to suppress lesion nematode populations, (Timper et al, 2005;Panaccione et al, 2006;Bacetty et al, 2009;Timper and Bouton 2012), whereas Kimmons et al (1990) found no difference in spiral nematode numbers in pots containing either endophytefree or endophyte-infected (toxic) tall fescue. Results from this study support this previous study, but we also show no difference between TMQ+ (AR584 novel endophyte) and TMQ2.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Ky312 is a poor host for stunt and ring nematodes, but a good host for spiral nematode. In previous work, the wild type endophyte has been shown to suppress lesion nematode populations, (Timper et al, 2005;Panaccione et al, 2006;Bacetty et al, 2009;Timper and Bouton 2012), whereas Kimmons et al (1990) found no difference in spiral nematode numbers in pots containing either endophytefree or endophyte-infected (toxic) tall fescue. Results from this study support this previous study, but we also show no difference between TMQ+ (AR584 novel endophyte) and TMQ2.…”
Section: Discussionmentioning
confidence: 92%
“…Ergot alkaloid-producing endophytes have been shown to reduce population densities of lesion nematode (Pratylenchus scribneri) (Panaccione et al, 2006;Bacetty et al, 2009), whereas novel endophyte resistance to lesion nematodes in summer-active cultivars was dependent on the endophyte strain and the tall fescue cultivar (Timper et al, 2005). Comparison of a transgenic nonergot alkaloidproducing strain (deletion of the dmaW gene encoding the first step of ergot alkaloid production) to the wild type strain showed endophyte-associated suppression of P. scribneri in perennial ryegrass was still evident suggesting other mechanisms might be responsible for the suppression (Panaccione et al, 2006). Reduction in root-knot nematode (Meloidogyne marylandi) population densities by ergot alkaloid-producing endophyte infected tall fescue plants has also been reported (Elmi et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…as those observed in ergot alkaloid producing strains (Timper et al, 2005). In contrast, other experiments showed that the amount of ergot alkaloids translocated to roots is very small, and experiments with Neotyphodium knockout mutants having their pathway of ergot alkaloid synthesis disrupted suggested that these alkaloids are not responsible for the inhibition of nematode populations in endophyte infected plants (Panaccione et al, 2006). Nevertheless, other types of alkaloids with antiherbivore activity are produced by Neotyphodium species, and chemical changes such as the production of phenolic compounds do occur in Neotyphodium-infected roots (Malinowski and Belesky, 2000).…”
Section: Interactions With Nematodesmentioning
confidence: 92%
“…Methanolic root extracts from E+ tall fescue Jesup (ergot alkaloid-producing endophyte; nonhost to P. scribneri) were nematostatic and repellant to P. scribneri when prepared from plants grown 45 d or more, whereas root extracts from E-tall fescue (no endophyte, susceptible plant) were attractive to the nematode (Bacetty et al, 2009a(Bacetty et al, , 2009b. Several purified ergot alkaloids, identified as compounds produced in Neotyphodiumassociated tall fescue and perennial ryegrass (Lolium perenne L.), were repellant to P. scribneri, and those that inhibited nematode motility were either nematotoxic or nematostatic (Panaccione et al, 2006;Bacetty et al, 2009aBacetty et al, , 2009b. It is interesting to note that even though alkaloids produced in the E+ plants could be nematotoxic, root extracts from these plants were not nematicidal to P. scribneri.…”
Section: Discussionmentioning
confidence: 99%